Transformative Constitutionalism and the Right to Health in Latin America - Rodolfo Gutiérrez Silva (Revista de Direito Sanitário)
The most important objective of transformative constitutionalism is to transform society by fostering democracy, protecting human rights, and seeking to eliminate poverty and reduce inequality. From this perspective, courts always guarantee this transformation through judicial activism. In order to achieve this objective, courts in the Latin American region are expanding their involvement in the health sector in particular. The objective of this article was to analyse the consequences of transformative constitutionalism in the health sector in Brazil, Argentina, Mexico and Colombia. The methodology applied was descriptive. Comparative, qualitative and literature review and 37 semi-structured interviews with judges, academics and public servants were carried out. Despite the progress made, the transformation achieved by the intervention of courts in the protection of the right to health has been only moderate. Transformative constitutionalism is generating internal and external transformations in the health sector of Latin America including direct material, symbolic and indirect transformations; however, there are still concerns about the negative consequences of transformative constitutionalism. Therefore, the promises of transformative constitutionalism remain very far to reach. In conclusion, courts should consider more the structural causes that are affecting health systems and strive more towards equilibrium.